Il terzo incontro GIT navigando tra geologia, GIS e strumenti IT - Redazione, Redazione (GEOmedia, 2008)
GIT's third meeting between geology, GIS and IT instruments GIT's (Geology and Information Technology - www.gitonline.eu) third meeting took place in the striking town of Offida, in the italian Marche region. The event presented interesting sessions dedicated to geological-IT issues. The 2008 edition featured more than 70 reports, comprising of "wine poster sessions" and traditional interventions by various professional and academic charachters.